2006
DOI: 10.1007/s10519-005-9038-3
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Temporal Descriptions of Open-field Behavior in Wild-derived Mouse Strains

Abstract: The open-field test is a commonly used apparatus in many behavioral studies. However, in most studies, temporal changes of details of behavior have been ignored. We thus examined open-field behavior as measured by both conventional indices and 12 ethograms supported by detailed temporal observation. To obtain a broader understanding, we used genetically diverse mouse strains: 10 wild-derived mouse strains (PGN2, BFM/2, HMI, CAST/Ei, NJL, BLG2, CHD, SWN, KJR, MSM), one strain derived from the so-called fancy mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 56 publications
2
49
1
2
Order By: Relevance
“…In the analyses of complex traits in wild-derived strains, we identified a marked diversity of phenotypes among strains [12,17,24,29]. The phenotypic diversity is believed to be a result of genetic diversity among wild-derived strains, as shown by several studies on genomic polymorphisms of these strains [17,18,20,23,27].…”
Section: Proposal Of a New Approach To Elucidate Complex Traitsmentioning
confidence: 95%
“…In the analyses of complex traits in wild-derived strains, we identified a marked diversity of phenotypes among strains [12,17,24,29]. The phenotypic diversity is believed to be a result of genetic diversity among wild-derived strains, as shown by several studies on genomic polymorphisms of these strains [17,18,20,23,27].…”
Section: Proposal Of a New Approach To Elucidate Complex Traitsmentioning
confidence: 95%
“…We bred several of these mutant lines for another generation and confirmed that the phenotypes were indeed heritable. PCA and factor analysis have been extensively used to study rodent behavior and have also been applied to QTL analysis for behavioral measures (30,(42)(43)(44). Use of multivariate analysis has led to the discovery of unique QTLs regulating latent behaviors that cannot be directly measured, such as fearfulness and anxiety (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…In order to study behavioral differences, a variety of behavioral analyses have been applied to the Mishima battery [10,14,22,25]. The results obtained in these studies are good examples of the usefulness of the Mishima battery.…”
Section: Behavioral Traits In Wild Strainsmentioning
confidence: 99%